2015
DOI: 10.1002/mus.24351
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal axonal swellings in painful and painless diabetic peripheral neuropathy

Abstract: There was no clinical relationship to pain or clinical neuropathy severity for axonal swellings in DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…[37] This is because there is controversy as to whether specific features of small fibre pathology in skin biopsies[38,39] may be related to painful neuropathy. [17,18,40,41]…”
Section: Discussionmentioning
confidence: 99%
“…[37] This is because there is controversy as to whether specific features of small fibre pathology in skin biopsies[38,39] may be related to painful neuropathy. [17,18,40,41]…”
Section: Discussionmentioning
confidence: 99%
“…However, Scheytt et al found no relationship between pain and GAP-43 reactivity in subjects with peripheral neuropathies of varying etiologies [52]. There are contradictory findings in studies investigating other IENF markers to differentiate painful- from painless-DPN including IENF length [50•, 53] and axonal swellings, which are measures of axonal degeneration [49, 54]. Levels within the skin of the neurotrophin nerve growth factor (NGF) were increased in patients with DPN and sensory symptoms, including pain, compared to painless-DPN [55].…”
Section: Cardiovascular Autonomic Neuropathymentioning
confidence: 99%
“…The main symptoms of diabetic neuropathy are tingling and numbness in the distal extremities sometimes accompanied by burning pain (Argoff et al 2006). Animal and human histochemical studies indicate that diabetes can cause dieback of PNS epidermal endings (Sorensen et al 2006; Cheng et al 2013; Cheung et al 2015; Ebenezer and Polydefkis 2014), an outcome that may not be related to pain (Sorensen et al 2006). Also, in studies where diabetes is modeled in animals, the development of ectopic activity in DRG neurons (Khan et al 2002; Serra et al 2012) has been demonstrated.…”
Section: 8 Ampk: Diabetic Neuropathy Prevention and Treatmentmentioning
confidence: 99%